ANALISIS ATAS KEBIJAKAN PEMERINTAH TENTANG BPJS DAN JKN MELALUI UU 36 TAHUN 2009 TENTANG KESEHATAN - Cucu Sugyati (TEMALI : Jurnal Pembangunan Sosial, 2018)
This study seeks to make a deep systematic analysis of the involvement of the community as an additional implementing element in the implementation of public health policy, especially in the field of mother and child in West Java, Indonesia. This descriptive-qualitative study presents a discussion of how the elements of public health practitioners interact with communities in West Java Province so that their knowledge and skills are needed. With the theory of health services, data obtained that (a) service and network cooperation in public health institutions, within the Provincial Government of West Java is quite uniform and well implemented; (b) in carrying out its obligations as the implementing element of the community deeply understand public policy in the field of public health, especially maternal and child health; so they can carry out their functions to serve the community. Nevertheless, the lack of community volunteers directly addressing maternal and child health is felt so that this review recommends incentives for health workers coming from ordinary people.